The Armenian apocalyptic tradition : a comparative perspective : essays presented in honor of Professor Robert W. Thomson on the occasion of his eightieth birthday - Bardakjian, Kevork B.; La Porta, Sergio.; Thomson, Robert W., 1934- (Studia in Veteris Testamenti Pseudepigrapha, 2014)
The Armenian Apocalyptic Tradition: A Comparative Perspective comprises a collection of essays on apocalyptic literature in the Armenian tradition. This collection is unprecedented in its subject and scope and employs a comparative approach that situates the Armenian apocalyptic tradition within a broader context. The topics in this volume include the role of apocalyptic literature and apocalypticism in the conversion of the Armenians to Christianity, apocalyptic ideology and holy war, the significance of the Book of Daniel in Armenian thought, the reception of the Apocalypse of Ps.-Methodius in Armenian, the role of apocalyptic literature in political ideologies, and the expression of apocalypticism in the visual arts.